Organizational Climate and Performance in Higher Education: A Bibliometric Analyses Using Dimensions Database - Amalou, Sif Islem (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This study conducts a comprehensive bibliometric analysis of research on organizational climate and performance in higher education. The analysis identifies a significant trend in publication patterns, noting a paucity of relevant studies from the early 1980s to 2016. However, from 2016 to 2023, there has been a consistent increase in the number of articles published, reflecting a growing recognition of the significance of organizational climate and performance in higher education. Most publications focus on trade, management, tourism, and services, with substantial contributions from education policy, sociology, philosophy, and related fields. Indonesia leads in publication output, followed by the USA, Malaysia, and Australia. The top-cited articles explore various topics, including the relationship between organizational culture, climate, and employee turnover, servant leadership approaches, university departmental climate, research excellence assessment, and trust dynamics. Although bibliometric analysis may not capture all research activities, this study provides valuable insights into the current research landscape. Future research directions may include investigating specific mechanisms linking organizational climate, work environment, satisfaction, and engagement across different sectors, examining the role of organizational behavior in employee productivity, and assessing and enhancing performance measurement systems.